Analisis Kesantunan Berbahasa dalam Video Animasi Pada Zaman Dahulu - Itsnaini Nur Khasanah; Riska Setyowati Siwi; Farida Ainur Rohmah; Rizqi Aji Wirastomo; Rizky Aprilia; Fitriani Nuraisah; Asep Purwo Yudi Utomo (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research examines language politeness which is an important skill that needs to be instilled early on to familiarize children in communicating politely. One effective method is through children's shows that apply the principles of language politeness. In the study, the researcher used the animated video "Pada Zaman Dahulu" as the medium of analysis. The researcher focuses on the ten principles of language politeness according to Leech which are manifested in the utterances of the Kancil and Monyet characters. The purpose of this research is to find out the language politeness of the two animated characters, namely Kancil and Monyet. The research method used is descriptive qualitative and pragmatics theoretical approach. The data were obtained from the animated series "Pada Zaman Dahulu" which consists of five videos with speech that is in accordance with language politeness. This study analyzes the compliance and violation of speech based on ten language politeness thimbles. The maxim found and analyzed include the generosity maxim, tact maxim, approbation maxim, modesty maxim, obligation of S to O maxim, obligation of O to S maxim, agreement maxim, opinion reticence maxim, sympathy maxim, and feeling reticence maxim. The number of the ten maxim will be presented in a table. Meanwhile, the data of the characters' speech in the animation that uses Malay language will be presented with the context as an explanation of the speech in order to facilitate data analysis and also facilitate readers in knowing the meaning of Malay language that is not yet understood so that readers can understand the analysis of language politeness in the animation "Pada Zaman Dahulu"